(untitled) (Journal of Informatics Education and Research, 2025)
The present study is based on secondary sources and try to understand the benefits from the kisan credit cards on marginal farmers and how the policy changes their social economic life. The study further focusses on whether the farmers are facing issues and problems while receiving the benefits of KCC. The Kisan Credit Card (KCC) Scheme was launched by NABARD in August 1998 to provide timely and affordable credit to farmers. Currently, the scheme is implemented through three main types of financial institutions: commercial banks, cooperative banks, and regional rural banks. The KCC functions as a revolving cash credit facility, allowing farmers to withdraw and repay funds as needed to meet their diverse agricultural credit requirements. By offering flexible and accessible credit, the KCC also plays a key role in strengthening the relationship between financial institutions and agricultural producers. According to NSSO (70th round) around 52 per cent of the farm households remained indebted in India as a whole of which the state of Andhra Pradesh had the highest share of indebted agricultural households in the country (92.9 per cent) and Tamil Nadu (82.5 per cent).